Distributed context Petri Nets : managing context interaction in distributed environments (2019)
Distributed systems allow interaction between multiple devices to take advantageof information each of them provides. In these type of systems, the use of context-oriented programming to allow them to dynamically adapt to context changes isan interesting possibility that currently has some limitations. Currently, context-oriented programming may introduce inconsistencies at run time when there aresimultaneous changes in the context. On a single system that uses context-orientedprogramming, a model to avoid such inconsistencies is context Petri nets. Butthis model was not designed for distributed systems.For this reason, we propose a new model, distributed context Petri nets, thatcan handle connections and disconnections of distributed nodes in dynamicallyadaptive software systems. This new model must behave as a distributed systemand represent its global state.We validate the approach by exploring all possible types of interactions betweencontexts as defined by context dependency relations. In these interactions weobserve the effects of node connection and disconnection, and how the systemdetects and solve inconsistencies that may arise